Safety of Computer Interpretation of Normal Triage Electrocardiograms. (January 2017) - Hughes, Katie E.; Lewis, Scott M.; Katz, Laurence; Jones, Jonathan
Abstract: Objectives: Frequent interruptions within the emergency department may lead to errors that negatively impact patient care. The immediate review of electrocardiograms (ECGs) obtained from triage patients is one source of interruption. Limiting triage ECGs requiring immediate attending review to those interpreted by the computer as abnormal may be one way to reduce interruption. We hypothesize that triage ECGs interpreted by the computer as "normal ECG" are unlikely to have clinical significance that would affect triage care. Methods: All triage ECGs performed at the University of North Carolina were collected between November 14, 2014, and March 3, 2015, according to a standard nursing triage protocol using GE machines running Marquette 12SL software. Triage ECGs with a computer interpretation of "normal ECG" were compared to an attending cardiologist's final interpretation. Triage ECGs for which the cardiologist's interpretation differed from the computer interpretation of normal ECG were presented to two emergency physicians (EPs) blinded to the goals of the study. The physicians were asked to evaluate the ECG for clinical significance. Clinical significance was defined as any change from normal that would alter triage care. Triage ECGs were considered true negatives if either the cardiologist agreed with the normal computer interpretation or if both EPs agreed that the ECG did not show clinical significance. Results: A total of 855 triage ECGs were collected over 16 weeks. A total of 222 (26%) were interpreted by the computer as normal. The negative predictive value for a triage ECGs interpreted by the computer as "normal" was calculated to be 99% (95% confidence interval = 97% to 99%). Of the ECGs with a computer interpretation of normal ECG, 13 had an interpretation by an attending cardiologist other than normal. Two attending EPs reviewed these triage ECGs. One of the 13 ECGs was found to have clinical significance that would alter triage care by one of the EPs. The stated triage intervention was "bed immediately." Conclusions: Our data suggest that triage ECGs identified by the computer as normal are unlikely to have clinical significance that would change triage care. Eliminating physician review of triage ECGs with a computer interpretation of normal may be a safe way to improve patient care by decreasing physician interruptions.